2019
DOI: 10.4103/ua.ua_62_18
|View full text |Cite
|
Sign up to set email alerts
|

Parents' awareness and knowledge of testicular torsion: A cross-sectional study

Abstract: Background:Testicular torsion (TT) is one of the most common emergencies in pediatric urology. Family awareness of this condition could lead to early diagnosis and intervention and salvage of the effected testicle. The purpose of this study is to assess parental awareness about TT and their source of knowledge. We also evaluated the response of the parents to their children's scrotal pain.Methods:A quantitative, observational, cross-sectional study was conducted from March 2017 to September 2017 at our institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…Our results are consistent with those obtained in the Alyami et al study; it found that as the number of boys in the family increases, the parents' awareness of TT also increases [8]. Parents with only girls in the family will not directly be impacted, but if they were aware of it, they might share the knowledge with other parents who have boys in their family since several studies have demonstrated that parents who were aware of testicular torsion mostly learned about it via friends, relatives, and the internet, which stands as the most common source of knowledge [8][9][10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with those obtained in the Alyami et al study; it found that as the number of boys in the family increases, the parents' awareness of TT also increases [8]. Parents with only girls in the family will not directly be impacted, but if they were aware of it, they might share the knowledge with other parents who have boys in their family since several studies have demonstrated that parents who were aware of testicular torsion mostly learned about it via friends, relatives, and the internet, which stands as the most common source of knowledge [8][9][10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 93%
“…A high-ridden testicle with an absent cremasteric reflex may be discovered on physical examination [7]. Detorsion within four to eight hours after symptom onset has typically been considered to be the ideal window of opportunity to salvage testicular function in individuals with testicular torsion [2,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline rate of orchiectomy for testicular torsion is already high at 34% based on a large US study [ 1 ]. Similarly, low patient and family awareness of testicular torsion is very common with only 15-30% of patients having prior knowledge of torsion in survey studies [ 12 , 13 ]. In our study, this was even lower with only 5% (8/156) of patients having prior knowledge of torsion.…”
Section: Discussionmentioning
confidence: 99%
“…Alyami et al. [ 22 ] surveyed 200 parents and found that only 19% of the parents whose children were patients in the pediatric urology clinic and 14% in the general pediatrics clinic were aware of the condition and its consequences. Comparable results were also reported by Friedman et al.…”
Section: Discussionmentioning
confidence: 99%